Development of recombinant inbred lines for fibre strength and other important traits in cotton (Gossypium hirsutum) - CHAUDHARY, BABITA; SINGH, JAGMAIL; CHOPRA, S K (The Indian Journal of Agricultural Sciences, 2010)
Field experiment was conducted during 2004–09 at New Delhi to develop recombinant inbred lines for fibre strength and other important fibre quality traits in cotton (Gossypium hirsutum L.). Most of the presently developed G. hirsutum cottons have low fibre strength. There is an urgent need to breed for high fibre strength to meet the demands of modern textile industry. High fibre strength line ‘Pusa 56-4’ was crossed with low fibre strength variety ‘RS 2013’ during 2004. Wide variation was observed in F2, F3 and F4 generations for fibre quality traits, especially fibre strength and also for seed cotton yield and important yield components. Transgressive segregation was observed for fibre strength, length and other traits. Ninety-three plants evaluated during 2008–09 in F4 generation showed more than 26 g/tex fibre strength and 30 plants out of these showed high yield ranging from 204.1 to 459.2 g/plant. All the 297 plants in F4 generation are being advanced to F6 generation for developing recombinant inbred lines. The cross presents good scope for simultaneous improvement of yield and fibre quality traits, especially fibre strength.